Gibberellins negatively modulate ovule number in plants - Gómez, María Dolores (2018)
Ovule formation is a complex developmental process in plants, with a strong impact on the production of seeds. Ovule primordia initiation is controlled by a gene network, including components of the signaling pathways of auxin, brassinosteroids and cytokinins. By contrast, gibberellins (GAs) and DELLA proteins, the negative regulators of GA signaling, have never been shown to be involved in ovule initiation. Here, we provide molecular and genetic evidence that points to DELLA proteins as novel players in the determination of ovule number in Arabidopsis and in species of agronomic interest, such as tomato and rapeseed, adding a new layer of complexity to this important developmental process. DELLA activity correlates positively with ovule number, acting as a positive factor for ovule initiation. In addition, ectopic expression of a dominant DELLA in the placenta is sufficient to increase ovule number. The role of DELLA proteins in ovule number does not appear to be related to auxin transport or signaling in the ovule primordia. Possible crosstalk between DELLA proteins and the molecular and hormonal network controlling ovule initiation is also discussed.